An intelligent approach to take care of mother and baby health - Mohammad Nasser Uddin; Mohammad Jahangir Alam; Md. Nurul Mustafa (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This is the era of technology and is widely used in every sector. In Bangladesh the use of technology is increasing day by day in many sectors. Health sector is one of them. This research is designed and developed to help the pregnant women to get weekly information on development and conditions of their health and the growing child inside their womb. This system will notify expectant mothers automatically   about their health checkup date and time. It provides general and special health information to the expectant mothers. It is designed with user friendly interface so that an expectant mother can use this system very effectively. This system allows a unique secure login system and provides a unique suggestion to the expectant mothers.This system is very user friendly and useful.